Analisis keputusan pembelian produk sayur kubis organik oleh konsumen di Kota Makassar - Andini Mughfira; Amal Said; Sulfiana Sulfiana; Helda Ibrahim (LP3M Universitas Putra Bangsa, 2026)
This study aims to analyze the factors influencing consumers’ purchasing decisions of organic cabbage in three modern markets in Makassar City, namely Gelael Supermarket, Hero Supermarket, and Indomaret Fresh. The research employed a quantitative approach with incidental sampling techniques involving 90 respondents. Data were analyzed using descriptive statistics and multiple linear regression. The results show that lifestyle, education, product quality, and price perception significantly affect purchasing decisions. Among these, product quality and price are the dominant determinants of consumer decisions. These findings suggest that marketing strategies for organic vegetables should emphasize quality and price affordability.